2017
DOI: 10.1002/anie.201708720
|View full text |Cite
|
Sign up to set email alerts
|

Ring Expansion, Photoisomerization, and Retrocyclization of 1,4,2‐Diazaboroles

Abstract: Diverse skeletal transformations of 1,4,2-diazaboroles through ring expansion, photoisomerization, and retrocyclization led to the isolation of various B,N-dihydroindole (compounds 3 and 6), 1,3-azaborolidin-2-imine (compound 7), and 1,4,2-diazaborol-3-imine derivatives (compound 11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 123 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, a similar reaction of the imino- N -heterocyclic carbene ligand with MesBBr 2 and subsequent reduction with an excess of KC 8 produced a B , N -dihydroindole derivative 342 as a white solid in 72% yield (Scheme ). They have proved that the formation of 342 from 341 proceeds via the intermediacy of the B -bromo-analogue of 1,4,2-diazaborole 340 .…”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…On the other hand, a similar reaction of the imino- N -heterocyclic carbene ligand with MesBBr 2 and subsequent reduction with an excess of KC 8 produced a B , N -dihydroindole derivative 342 as a white solid in 72% yield (Scheme ). They have proved that the formation of 342 from 341 proceeds via the intermediacy of the B -bromo-analogue of 1,4,2-diazaborole 340 .…”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…Thep air of bulky Fmes groups at boron and the remaining Xyl aryl group at nitrogen are oriented close to perpendicular to the core.T he B1-N2-B2 subunit is delocalized (B1ÀN2:1 .420(2) ,N 2 ÀB2:1 .440( 2) )a si st he opposite N1-C2-C3 enamine unit (C2ÀC3:1 .337(2) ,N 1 À C2:1.371( 2) ). Consequently,the central connecting N2ÀC2 linkage is long at 1.440 (2) .…”
Section: Methodsmentioning
confidence: 99%
“…Kinjo et al described the first derivatives of this rare class of compounds in 2015. [2] They prepared them starting from the imino-functionalized N-heterocyclic carbene precursors 1.T othe best of our knowledge,n oa dditional principal entry into this class of aromatic five-membered BNN heterocycles has been reported. We have now developed anew pathway to examples of the dihydro-1,4,2-diazaborole family and to the oxygen and sulfur analogues (4,5), the BN isosteres of furan and thiophen, and even of the BN indolizine derivative 6 (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, very limited methods have implemented this process (Figure 1B). [8] In 2017, Kinjo and co‐workers reported that the insertion of extremely active bromoborylene (BrB:) into the C−N bond achieved N ‐heterocycle enlargement [8a] . In 2019, Yorimitsu's group achieved skeletal editing of indoles to 1,2‐benzazaborines through indole reductive ring‐opening with lithium metal to form dianionic species and subsequent organoboronic esters trapping [8b] .…”
Section: Figurementioning
confidence: 99%